Keeping pace with current issues in reporting suicide and mental illness - Skehan, J.; Burns, L.; Hazell, T. (Journal of University Teaching and Learning Practice, 2007)
The Response Ability Project, funded under the Mindframe National Media Initiative inAustralia, seeks to influence tertiary curricula so that graduates in journalism will beaware of and able to respond appropriately to issues relating to suicide and mentalillness. Whilst the initial multi-media resources developed to support journalismeducators have been received well, engagement with media organisations andindividual journalists under other Mindframe projects have revealed further complexitiesassociated with the reporting of suicide and mental illness. In particular, journalistshave indicated that the issues become more problematic when they are required toreport suicides in other contexts, such as murder-suicides, deaths in custody andvoluntary euthanasia. Similarly, the reporting of mental illness was more complex in thecontext of crime and in the reporting of the mental health care system. This paper willhighlight some of these new complexities of reporting and discuss how the ResponseAbility project has responded through the development of supplementary resources toallow educators to raise such issues with students.